Feedback based scheduling algorithm - An OBS simulation framework - Liu, Haibin. (2008)
Feedback based scheduling algorithm to resolve contention in optical backbone network is proposed. The new algorithm is to reduce the high loss rate in optical burst switching (OBS), which makes OBS more practical. A simulation framework on Network Simulator 2 (NS2) is built which includes implementations of multiple wavelengths.